Studi Pengelolaan Koleksi Manuskrip di Museum Negeri Provinsi Sulawesi Tengah - Faat, Afril Randa Mafia; Syamsuri, Syamsuri; Sairin, Mohammad (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2023)
This research examines the management of manuscript collections at the Central Sulawesi Provincial State Museum as an effort to preserve Indonesia's cultural heritage. The aim of this study is to understand the process of managing manuscript collections at the Central Sulawesi Provincial State Museum. This research adopts a qualitative descriptive approach, utilizing data collection techniques such as interviews, observations, and documentary studies. The data analysis techniques employed encompass data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the manuscript collections at the Central Sulawesi Provincial State Museum serve a dual role as references and sources of knowledge for visitors. Despite the collection comprising over 45 items, only 25 have been inventoried. The management involves crucial stages such as registration, inventorying, classification, cataloging, and physical preservation, including conservation through fumigation and digitization. A survey and research team was formed to identify collections from the community, originating from various regions within Central Sulawesi. Meticulous management is essential to ensure that the information within the manuscripts remains accessible to the public and researchers. Both internal and external supporting factors, including the value of the collection and legal regulations, provide robust backing. However, challenges such as a lack of trained human resources, limited facilities, conservation obstacles, and budget constraints also impact collection management. This research underscores the necessity of collaboration in overcoming these challenges and maximizing the management of manuscript collections to preserve this valuable cultural heritage. Abstrak Penelitian ini mengkaji tentang pengelolaan koleksi manuskrip di Museum Negeri Provinsi Sulawesi Tengah sebagai upaya melestarikan warisan budaya Indonesia. Tujuan penelitian ini untuk mengetahui proses pengelolaan koleksi manuskrip di Museum Negeri Provinsi Sulawesi Tengah. Penelitian ini merupakan penelitian deskriptif kualitatif, teknik pengumpulan data melalui wawancara, observasi, dan studi dokumentasi, teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukan bahwa koleksi manuskrip di Museum Negeri Provinsi Sulawesi Tengah memiliki peran ganda sebagai referensi dan sumber ilmu pengetahuan bagi pengunjung. Meskipun koleksi manuskrip mencapai lebih dari 45, hanya 25 yang diinventarisasi. Pengelolaannya melibatkan tahapan penting seperti registrasi, inventarisasi, klasifikasi, katalogisasi, dan perawatan fisik, termasuk konservasi melalui fumigasi dan digitalisasi. Tim survei dan penelitian dibentuk untuk mengidentifikasi koleksi dari masyarakat, yang berasal dari berbagai wilayah Sulawesi Tengah. Pengelolaan yang teliti sangat penting agar informasi dalam manuskrip tetap dapat diakses oleh masyarakat dan peneliti. Faktor pendukung internal dan eksternal, termasuk nilai koleksi dan regulasi hukum, memberikan dukungan yang kuat. Namun, kendala seperti kurangnya SDM terlatih, keterbatasan sarana, hambatan dalam konservasi, dan terbatasnya anggaran juga mempengaruhi pengelolaan koleksi. Penelitian ini menekankan perlunya kolaborasi dalam mengatasi hambatan dan memaksimalkan pengelolaan koleksi manuskrip untuk melestarikan warisan budaya yang berharga.